2021
DOI: 10.3389/fneur.2021.629257
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HIV-Associated Neurocognitive Impairment in Middle-Aged and Older Persons With HIV in Lima, Peru

Abstract: Background: With widespread use of antiretroviral medications, people living with HIV (PWH) are living longer worldwide, increasing their risk of developing neurocognitive impairment (NCI). The proportion of Peruvians over age 60 is expected to increase to 25% of the population by 2050, including PWH. Therefore, the problem of aging and NCI, especially in the setting of HIV infection, is uniquely pressing. We sought to study the rates of and risk factors associated with NCI among middle-aged and older PWH in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
2
1
Order By: Relevance
“…The highest odds in the present study were seen comparing populations aged 35 to 44 years to those 85 and older for both time periods. Previous research has shown that HIV is the most prevalent cause of dementia among younger adults 3,24,25 ; however, research tends to focus on middle-aged and older adults with respect to HAD assessments 26,27 . Nevertheless, the present study shows that HAD is of crucial concern among younger populations.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The highest odds in the present study were seen comparing populations aged 35 to 44 years to those 85 and older for both time periods. Previous research has shown that HIV is the most prevalent cause of dementia among younger adults 3,24,25 ; however, research tends to focus on middle-aged and older adults with respect to HAD assessments 26,27 . Nevertheless, the present study shows that HAD is of crucial concern among younger populations.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous research has shown that HIV is the most prevalent cause of dementia among younger adults 3,24,25 ; however, research tends to focus on middle-aged and older adults with respect to HAD assessments. 26,27 Nevertheless, the present study shows that HAD is of crucial concern among younger populations. Although there are HIV intervention and prevention programs geared toward youth [28][29][30] and there has been increasing attention paid to older adults, 31,32 middle-aged adults are sometimes forgotten with respect to HIV prevention and intervention programs.…”
Section: Discussionmentioning
confidence: 53%
“…Finally, people diagnosed with HAD have a performance of 2 SD below the mean in two cognitive domains and evident difficulty in the achievement of day-to-day activities [ 3 , 6 ]. HAND causes a spectrum of cognitive impairment, motor dysfunction, and behavioral and emotional disorders [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%